Barriers to social participation among lonely older adults: the influence of social fears and identity. - Johanna C Goll; Georgina Charlesworth; Katrina Scior; Joshua Stott (PLoS ONE, 2015)
Introduction Loneliness among older adults is a major public health problem that may be associated with processes of social participation and identity. This study therefore sought to examine the relationship between social participation and identity in a sample of lonely older adults living independently in London, England. Method An inductive qualitative approach, based on semi-structured interviews and thematic analysis, was employed. Results Participants commonly spoke of barriers to social participation that have been reported elsewhere, including illness/disability, loss of contact with friends/relatives, lack of a supportive community, and lack of acceptable social opportunities. However, novel findings were also derived. In particular, participants commonly minimised the difficulties they faced alone, and described attempts to avoid social opportunities. These behaviours were linked to fears about engaging in social participation opportunities, including fears of social rejection and/or exploitation, and fears of losing valued aspects of identity. Discussion It is concluded that social participation amongst lonely older people will not improve through the removal of previously reported barriers alone; instead, older peoples' beliefs, fears and identities must be addressed. Suggestions for implementing these findings within community organisations are provided.